Do financial advisors exploit responsible investment preferences? - Marten Laudi; Paul Smeets; Utz Weitzel (Tinbergen Institute, 2021)
An unprecedented number of investors are giving their financial advisors a mandate for socially responsible investing (SRI). Yet, the impact of SRI mandates on consumers is unclear. In a pre-registered lab-in-the-field experiment with 345 professional advisors, we find that advisors charge a premium to SRI clients that cannot be justified by higher effort, skill, or costs. This suggests that advisors exploit the SRI preferences of their clients (who accept these higher fees). In an independent survey, financial regulators predict higher SRI fees but do not predict exploitation. Regulators confirm that our findings are externally valid and require attention from policymakers.
Keywords: C93; G11; 330; Experimental Finance; Financial Advice; Socially Responsible Investments